Continuity properties of solutions of multivalued equations with white noise perturbation. (1997) - Michta, Mariusz
Abstract : In the paper, we consider a set-valued stochastic equation with stochastic perturbation in a Banach space. We prove first the existence theorem and then study continuity properties of solutions.